Relational Morphology: A Cousin of Construction Grammar - Jackendoff, Ray; Audring, Jenny (Frontiers in Psychology, 2020)
Relational Morphology (RM) is a novel approach to word structure that bears a close relation to Construction Grammar (CxG). Based on the Parallel Architecture framework, its basic question is: What linguistic entities are stored in long-term memory, and in what form? Like CxG, RM situates the “rules of grammar” in an extended lexicon, right along with words, multiword expressions such as idioms and collocations, and meaningful syntactic constructions. However, its notion of schema enriches CxG’s notion of construction in a number of respects, including (a) the possibility of purely formal schemas that lack meaning, (b) a more precise way of specifying relations among lexical items than standard inheritance, (c) the possibility of “horizontal” relations between individual words and between schemas, (d) a clearer characterization of the distinction between productive and nonproductive phenomena, and (e) more explicit integration with theories of language processing and of other domains of cognition.